Environmental risk assessment of wastewaters from printed circuit board production: A multibiomarker approach using human cells. (February 2017) - Gerić, Marko; Gajski, Goran; Oreščanin, Višnja; Domijan, Ana-Marija; Kollar, Robert; Garaj-Vrhovac, Vera
Abstract: Since the production of printed circuit boards (PCBs) generates wastewater contaminated with heavy metals and organic matter, PCB factories represent potential pollution sites. The wastewater toxicologically tested in this study contained several metals and the most abundant were copper and iron. At two exposure times tested (4 and 24 h) PCB wastewater (PCBW) proved to be cytotoxic (decreased cell viability) and genotoxic (increased comet assay tail intensity and tail moment) to human blood peripheral lymphocytes in vitro, and the oxidative stress parameter (malondialdehyde concentration) was also found to be higher. After application of combined treatment by waste base, ozone and waste sludge methods, concentrations of metals in purified PCBW were below the upper permitted levels and all tested toxicological parameters did not differ compared to the negative control. Taken together, similar methods could be implemented in PCB factories before discharging potentially toxic wastewater into the environment because purified PCBW does not represent a threat from the aspect of cytotoxicity and genotoxicity. Graphical abstract: Highlights: Printed circuit board production generates wastewater containing heavy metals. Results on human cells suggest that wastewater could be cyto/genotoxic. At the same time wastewater increased parameters of oxidative stress. After wastewater purification, all parameters tested were in control values range. Similar treatment methods should be applied before discharge of wastewater.